2019
DOI: 10.1016/j.heliyon.2019.e01419
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric levels of BPA associated with particulate matter in an urban environment

Abstract: Bisphenol A (BPA) is an Endocrine disruptor compound (EDC), capable of interfering with hormone related pathways and cause adverse effects, for example, in the reproductive system in wildlife and humans. As it has multiple applications and uses, mainly in the manufacturing of plastic and resin products, increasing amounts are being released into the environment with resulting enhanced exposure pathways. Since negative effects have been demonstrated even at low doses, it has been increasingly studied. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
16
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 38 publications
(65 reference statements)
2
16
1
1
Order By: Relevance
“…Woerden [5], Karrer [6] and many scholars also obtained similar research conclusions [7]. It has been proved that BPA exists mainly in natural waters, sediments, soil, as well as sewage and wastewater sludge, with a concentration ranging from nanogram to microgram level [8][9][10], posing a greater threat to humans and animals. After entering human body, BPA can disrupt normal cellular functions by acting as an estrogen agonist and an androgen antagonist [11].…”
Section: Introductionmentioning
confidence: 73%
“…Woerden [5], Karrer [6] and many scholars also obtained similar research conclusions [7]. It has been proved that BPA exists mainly in natural waters, sediments, soil, as well as sewage and wastewater sludge, with a concentration ranging from nanogram to microgram level [8][9][10], posing a greater threat to humans and animals. After entering human body, BPA can disrupt normal cellular functions by acting as an estrogen agonist and an androgen antagonist [11].…”
Section: Introductionmentioning
confidence: 73%
“…Recent studies revealed that BPA is present in indoor dust [21], and its content in the o ce room is 5 to 10 times more than that in the living room [22]. Increasing amounts of BPA are being released into the atmospheric environment especially in industrial areas and city centers [23].…”
Section: Introductionmentioning
confidence: 99%
“…Usually, BPA can be eliminated through traditional physical, chemical or biological treatments, such as solvent extraction, photochemical degradation, biodegradation, etc [3]. As a pollutant in solution, BPA usually is in low concentration from µg/L to mg/L and it is time-consuming or uneconomical to get rid of BPA with those traditional methods above [4,5]. New techniques should be explored to remove BPA more efficiently from wastewater and water sources.…”
Section: Introductionmentioning
confidence: 99%